Urinary incontinence in the elderly: A comprehensive review of epidemiology, biopathology, clinical manifestations, diagnosis, and treatment - Rocha, Gabriel Candido da; Oliveira, Carlos Walmyr de Mattos; Lorenzetti, Willian; Valentim, Laenne Ágata; Rocha , Wolney Peres da; Soares , Thays Ferraz; Santana, Victor Augusto Souza; Miklós, João Paulo Ortiz; Pires, Isabella Messias; Ferreira, Anna Carolline Pimenta; Jesus , Yngrid Priscilla Gomes de; Jesus, Luana Samara Maia de; et al. (Seven Editora, 2024)
This study presents a comprehensive review of geriatric urinary incontinence, addressing its subtypes, epidemiology, biopathology, causes in the elderly, transient considerations, functional urinary incontinence, clinical manifestations, diagnosis, and treatment options. The survey, conducted from November 2023 to February 2024, used a systematic approach across biomedical databases, including PubMed, Scopus, and Google Scholar. Relevant search terms were applied, such as "geriatric urinary incontinence", "urge incontinence", "stress incontinence", among others. There was no restriction of language or date of publication in the selection of studies. The literature review highlights that urinary incontinence, characterized by the involuntary extravasation of urine, predominantly affects women and increases with age. It is estimated that up to one-third of community-dwelling older adults and half of hospitalized patients suffer from transient incontinence. The associated costs in the U.S. exceed 83 billion annually. In addition to the financial impacts, incontinence can lead to serious physical complications and emotional impacts, such as shame and social isolation. The biopathology of urinary incontinence in the elderly involves changes in the detrusor muscle, urethral changes, and prostatic obstruction in men, in addition to neurological factors. Overactivity of the detrusor muscle is the most common cause, followed by stress urinary incontinence and urethral obstruction in men. Functional urinary incontinence, associated with cognition and mobility deficits, is another relevant type. Diagnosis involves clinical evaluation, voiding diary and, in some cases, urodynamic evaluation for complex cases. Treatment encompasses behavioral therapy, pharmacotherapy, and surgical procedures. Behavioral therapy, including voiding habit re-education and pelvic floor exercises, is an essential approach. Medications, such as anticholinergics and mirabegrone, are modestly effective but can have side effects, especially in the elderly. Surgical procedures, such as urethral sling and neuromodulation, are options for severe or refractory cases. This review highlights the importance of a comprehensive understanding of geriatric urinary incontinence, not only because of its prevalence and social impacts, but also because of the variety of causes and treatment options available. Future directions for research include further investigations into the efficacy and safety of existing therapies, especially in elderly populations. DOI:https://doi.org/10.56238/sevened2024.010-004